LCD Imitation Media As a Learning Support in Improving Children's Creative Thinking Skills - Siti Rohmatul Jannah; Maulida Rizqi Istiqomah; Savira Aisah Purwandini; Faiqotul Hima Mahfidah; Novita Ahriani; Julianto Julianto; Heru Subrata; Suprayitno Suprayitno (Jurnal Pendidikan Jompa Indonesia, 2023)
The development of education in the 21st century encourages educators to do various creative ways in designing learning media. Not only required to be creative in designing learning media, but also required to be creative in utilizing the items around us. What is expected with the existence of learning media is to be able to increase the creativity of teachers and students in comfortable and effective learning. It would be much better if the designed media was able to utilize used items in the local environment. So that it can educate about environmental care attitudes to students. The purpose of this writing is to introduce LCD imitation media and educate the use of used goods as a medium to support learning and can improve students' creative thinking skills. The method used is a literature study that takes data from various sources of articles, journals and books offline and online. This LCD imitation media had participated in exhibitions held in the department. From the exhibition, researchers received feedback from student visitors and lecturers, and received a very constructive response in the development of this LCD imitation media for the better.